A Comparative Study between Rousseau and Ayatullah Javadi Amoli on the Purposes of Moral Education: Accommodation between Naturalism and Revelation - Mahmoud Omidi; Mohammad Hassan Mirzamohmmadi; Ghader Faraghi (اخلاق وحیانی)
Morality and ethical research method of this study is comparative analysis. The findings of the research indicate that the ultimate goal of moral education in Rousseau's naturalistic system is human obedience to nature, and in Ayatullah Javadi Amoli's revelation-based system is man's rapprochement with God. In order to achieve such an aim, Rousseau recognized self-care, temperance, humility, the realization of freedom and altruism as intermediate goals, and Ayatollah Javadi recognizes God-knowledge, self-knowledge, Fitrah-seeking, humility and moderation, dignity, the education in the present age are the most fundamental human issues that have always been of interest to thinkers and scholars from all over the world. Therefore, the present study aims to compare the goals of ethical education from the perspective of Rousseau and Ayatollah Javadi Amoli. The realization of freedom, and altruism as intermediate goals. There are shared aspects in the goals introduced by the two thinkers, one of the most important of which is the special attention to moral education. But the most important matter of disagreement between the two is that Rousseau considers staying away from society is the way to achieve ethical goals, while according to Professor Javadi Amoli, achievement of such goals should be come about within the society. Also, the centrality of nature on the one hand, and Allah Almighty, on the other hand, is one of the most important differences between them and epistemic sources of moral education goals in two perspectives that manages the ethical orientation of man from beginning to end.